Lu Xun as the Great Master: An Interview with Li Jing. (3rd July 2019) - Liu, Hongtao; Hull, David N. C.
Abstract : In this January 2019 interview with Li Jing, the playwright of Lu Xun, Professor Liu Hongtao from Beijing Normal University delves into how a "drama rookie" ended up writing such a groundbreaking award-winning script. They discuss her exhaustive research and the lessons she learned struggling with how to write a character that is already so firmly entrenched in the cultural consciousness.